Burnout among doctors in China through 2020: A systematic review and meta-analysis. Issue 7 (July 2022) - Zheng, Qin; Yang, Kun; Zhao, Rui-Jie; Wang, Xue; Ping, Ping; Ou, Zheng-Hang; Su, Xiao-Peng; Zhang, Jing; Qu, Miao
Abstract: Objective: To analyze surveys measuring the prevalence of burnout among Chinese doctors and reveal the overall prevalence, characteristics, timeline, and factors related to burnout. Methods: A comprehensive search was conducted on China National Knowledge Infrastructure, WANFANG, PubMed, EMBASE, PsycINFO and Cochrane Library databases from their inception to 28 February 2021. Random-effects meta-analyses, meta-regression and planned subgroup analyses were performed, and the standardized mean difference was adopted for comparisons between subgroups. Egger's and Begg's tests were performed to evaluate publication bias. Heterogeneity across the studies was tested using the I 2 statistic. The study protocol was registered on PROSPERO (CRD42018104249). Results: In total, 3, 210 records were reviewed; 64 studies including 48, 638 Chinese doctors were eligible for meta-analysis. The prevalence of burnout increased continuously from 2008 to 2017 and decreased significantly from 2018 to 2020, a little increase from 2020 to 2021. The overall prevalence of burnout was 75.48% (95% CI, 69.20 to 81.26; I 2 = 99.23%, P < 0.001), and high burnout was 9.37% (95% CI, 4.91 to 15.05, I 2 = 98.88%, P < 0.001). The prevalence of emotional exhaustion was 48.64% (95% CI, 38.73 to 58.59; I 2 = 99.53%, P < 0.001), depersonalization was 54.67% (95% CI, 46.95 to 62.27; I 2 = 99.20%, P < 0.001), and reduced personal accomplishment was 66.53% (95% CI, 58.13 to 74.44; I 2 = 99.37%, P < 0.001). Gender, marriage, professional title and specialty all influenced burnout. Conclusions: The results showed that the total prevalence of doctor burnout in China is very high. The prevalence of burnout varies by location. Gender, marital status and professional title all affect burnout scores. Abstract : Burnout; Prevalence; Chinese doctor; Systematic review; Meta-analysis.